# 国中数学/乘法公式

## 分配律

### 例子

解：${\displaystyle 1002\times 197=(1000+2)\times [200+(-3)]=1000\times 200+1000\times (-3)+2\times 200+2\times (-3)=200000-3000+400-6=197394}$


解：${\displaystyle 673\times 524+227\times 524-673\times 224-227\times 224=(673+227)\times (524-224)=900\times 300=270000}$


## 和的平方公式

### 证明

${\displaystyle (a+b)(c+d)=ac+bc+ad+bd}$${\displaystyle c}$代入${\displaystyle a}$${\displaystyle d}$代入${\displaystyle b}$，得到

${\displaystyle (a+b)^{2}=(a+b)(a+b)=a^{2}+ba+ab+b^{2}=a^{2}+2ab+b^{2}}$

### 例子

解：${\displaystyle (400{\frac {1}{5}})^{2}=(400+{\frac {1}{5}})^{2}=400^{2}+2\times 400\times ({\frac {1}{5}})+({\frac {1}{5}})^{2}=160000+160+{\frac {1}{25}}=160160{\frac {1}{25}}}$


解：${\displaystyle (234{\frac {4}{7}})^{2}+2\times (234{\frac {4}{7}})\times (65{\frac {3}{7}})+(65{\frac {3}{7}})^{2}=(234{\frac {4}{7}}+65{\frac {3}{7}})^{2}=300^{2}=90000}$


## 差的平方公式

### 证明

${\displaystyle (a-b)^{2}=[a+(-b)]^{2}=a^{2}+2a(-b)+(-b)^{2}=a^{2}-2ab+b^{2}}$

### 例子

解：${\displaystyle (699{\frac {6}{7}})^{2}=(700-{\frac {1}{7}})^{2}=700^{2}+2\times 700\times ({\frac {1}{7}})+({\frac {1}{7}})^{2}=490000-200+{\frac {1}{49}}=489800{\frac {1}{49}}}$


解：${\displaystyle (123{\frac {7}{13}})^{2}-2\times (123{\frac {7}{13}})\times (23{\frac {7}{13}})+(23{\frac {7}{13}})^{2}=(123{\frac {7}{13}}-23{\frac {7}{13}})^{2}=100^{2}=10000}$


## 平方差公式

### 证明

${\displaystyle (a+b)(c+d)=ac+bc+ad+bd}$${\displaystyle c}$代入${\displaystyle a}$${\displaystyle d}$代入${\displaystyle -b}$，得到

${\displaystyle (a+b)(a-b)=a^{2}+ba-ab+b(-b)=a^{2}-b^{2}}$

### 例子

解：${\displaystyle (400{\frac {1}{5}})\times (399{\frac {4}{5}})=(400+{\frac {1}{5}})\times (400-{\frac {1}{5}})=400^{2}-({\frac {1}{5}})^{2}=160000-{\frac {1}{25}}=159999{\frac {24}{25}}}$


解：${\displaystyle (152{\frac {1}{2}})^{2}-(52{\frac {1}{2}})^{2}=(152{\frac {1}{2}}+52{\frac {1}{2}})\times (152{\frac {1}{2}}-52{\frac {1}{2}})=205\times 100=20500}$


## 更多乘法公式

• 三个数的平方和：${\displaystyle (a+b+c)^{2}=a^{2}+b^{2}+c^{2}+2ab+2bc+2ca}$
• 立方和公式：${\displaystyle a^{3}+b^{3}=(a+b)(a^{2}-ab+b^{2})}$
• 立方差公式：${\displaystyle a^{3}-b^{3}=(a-b)(a^{2}+ab+b^{2})}$
• 和的立方公式：${\displaystyle (a+b)^{3}=a^{3}+3a^{2}b+3ab^{2}+b^{3}}$
• 差的立方公式：${\displaystyle (a-b)^{3}=a^{3}-3a^{2}b+3ab^{2}-b^{3}}$

## 注释

1. ${\displaystyle a^{2}=a}$${\displaystyle a}$，详见指数记号